Railway Photographic Advertising in Britain, 1900-1939 - Medcalf, Alexander (Palgrave Studies in the History of the Media, 2018)
This book explores the phenomenal resources dedicated to understanding and encouraging passengers to consume travel from 1900 to 1939, analysing how place and travel were presented for sale. Using the Great Western Railway as a chief case study, as well as a range of its competitors both on and off the rails, Alexander Medcalf unravels the complex and ever-changing processes behind corporate sales communications. This volume analyses exactly how the company pictured passengers in the countryside, at the seaside, in the urban landscape and in the company's vehicles. This thematic approach brings transport and business history thoroughly in line with tourism and leisure history as well as studies in visual culture.